2022
DOI: 10.1111/josi.12545
|View full text |Cite
|
Sign up to set email alerts
|

Reducing ageism toward older adults and highlighting older adults as contributors during the COVID‐19 pandemic

Abstract: The COVID‐19 pandemic exacerbated ageism (stereotyping, prejudice, and discrimination) toward older adults in the United States, highlighting the belief that older adults are a burden. Prior to the pandemic, a growing body of research sought to reduce ageism using the PEACE (Positive Education about Aging and Contact Experiences) model. Extending that research, participants were randomly assigned to watch three videos (less than 10 min total) that challenged stereotypes about aging and older adults, depicted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 93 publications
0
27
0
Order By: Relevance
“…Stereotypes about older people are ambivalent and, thus, encompass positive and negative traits, such as being perceived as poor in health and fragile, warm but incompetent, inflexible and lacking of competitiveness but friendly and lovely grandparents, wise but dispensable individuals unable to contribute to society (e.g., review of international literature in Cuddy & Fiske, 2002 ; Fiske et al., 2002 ; Levy & Banaji, 2002 ; Raina & Balodi, 2014 ). The normalization and perpetuation of stereotypes is facilitated by mass media too, which often portray older individuals in a stereotyped manner as narrow‐minded, fragile, diseased, and incompetent (Cuddy et al., 2005 ; Levy and Banaji, 2002 ; American participants in Lytle & Levy, 2019 ; Raina & Balodi, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotypes about older people are ambivalent and, thus, encompass positive and negative traits, such as being perceived as poor in health and fragile, warm but incompetent, inflexible and lacking of competitiveness but friendly and lovely grandparents, wise but dispensable individuals unable to contribute to society (e.g., review of international literature in Cuddy & Fiske, 2002 ; Fiske et al., 2002 ; Levy & Banaji, 2002 ; Raina & Balodi, 2014 ). The normalization and perpetuation of stereotypes is facilitated by mass media too, which often portray older individuals in a stereotyped manner as narrow‐minded, fragile, diseased, and incompetent (Cuddy et al., 2005 ; Levy and Banaji, 2002 ; American participants in Lytle & Levy, 2019 ; Raina & Balodi, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…As for discrimination against older people, it emerged in a variety of life‐domains such as interpersonal communications, politics, workplace, and healthcare (for reviews of international literature see Lytle & Levy, 2019 ; Mucchi Faina, 2013 ; Ng, 1998 ; Raina & Balodi, 2014 ; for recent research on discrimination during the pandemic see Lloyd‐Sherlock et al., 2022 ). In workplace, older people are devalued in their competence and potentials and, thus, they often experience a lack of work opportunities (e.g., Abrams et al., 2016 ; systematic review conducted on data from 45 countries in Chang et al., 2020 ; North & Fiske, 2016 ; Raina & Balodi, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research highlights that the COVID-19 health and safety measures have led to increased mental health problems, such as increased feelings of depression, anxiety, social isolation, and loneliness, potentially cognitive decline (Allen et al 2021;Bailey et al, 2021;Dahlberg, 2021;Derrer-Merk et al, 2022b;Derrer-Merk et al, 2022a;Heidinger & Richter, 2020;Richter & Heidinger, 2021;Krendl & Perry, 2021;Litwin & Levinsky, 2021;De Pue et al 2021;Shahid et al, 2020;Smith et al, 2020;Cohn-Schwartz et al, 2022;Tsoukalis-Chaikalis et al, 2021;van Gerwen et al, 2021;Victor et al, 2022;Vrach &Tomar, 2020). Other studies reported the consequences of age discrimination (Derrer-Merk et al, 2022c;Lytle & Levy, 2022;MCDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022;Sutter et al, 2022;Swift & Chasteen, 2021;). Risk communication and how it is perceived by society are also important aspects of risk management in a pandemic such as COVID-19 (Sandman, 2003(Sandman, , 2022.…”
Section: Introductionmentioning
confidence: 99%
“…At other times, it is used as a tool that facilitates interpretation and the production of meaning. In any event, qualitative content analysis can provide descriptions and interpretations (Lindgren et al., 2020 ). In this study, we mainly used this method to describe and compare the relevant data from each campaign.…”
Section: Methodsmentioning
confidence: 99%